Development of "Material Gaya" Teaching Materials Based on Creative Science Videos (CSV) for Class VIII Junior High School Students - Anjarwati, Sulis; Darmayanti, Rani; Khoirudin, M (JEMS: Jurnal Edukasi Matematika dan Sains, 2023)
Teaching materials are a resource for teachers and students to carry out the learning process. Therefore, it is necessary to develop innovative teaching materials that enable students to achieve superior learning outcomes. One of the innovative and creative teaching materials is Creative Science Video-Based Teaching Materials (CSV). In this study, we aim to commercialize creative science teaching materials by using videos as style teaching materials. We also assess product quality based on materials and media reports. The research variables were validated by material, expert and video experts. In addition, the professional quality of audiovisual media has great potential. This research is an R n D with statistical evaluation results of material expert verification by CSV type reaching 3.62, media experts reaching 3.84. Therefore, the conclusion of this study is that science teaching materials such as style teaching materials can be developed through Creative Science Video-Based Teaching Materials (CSV)